Advances in metabolic disorders : Vol. - 3 - Levine, Rachmiel, 1910-; Luft, Rolf, 1914- (New York : Academic Press, 1968)
Vol. 7 includes the Proceedings of a Symposium on Insulin, held at the City of Hope Medical Center, Duarte, California, 1972.
Editors: 1964-<78> R. Levine and R. Luft.
Includes Index.
Biological abstracts
Energy research abstracts
Life sciences collection
Bibliography of agriculture
Keywords: Metabolism -- Disorders -- Periodicals; Metabolism -- Periodicals